2022
DOI: 10.1177/10781552221079786
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Potential Drug-Drug Interactions in Pediatric and Adolescent Patients Receiving Chemotherapy

Abstract: Introduction Pediatric and adolescent oncology patients admitted to receive chemotherapy are at risk for drug-drug interactions (DDI). While adult literature has quoted this risk to be as high as 95% of encounters, the literature in pediatrics is limited. This is a single-center, retrospective chart review of DDI in hospitalized pediatric oncology patients. Methods All patients admitted to Texas Children's Hospital for chemotherapy were included. Medications ordered during the hospitalization were evaluated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
(22 reference statements)
1
0
0
Order By: Relevance
“…18 According to recent data, a retrospective data analysis study using the Pediatric Health Information System (PHIS) database, which included data from 498,956 hospitalized children from 43 different hospitals, found that 49% of hospitalizations in hospitalized pediatric patients were associated with ≥1 potential DDI. 19 Similar results were obtained in a study conducted by Daignault et al 20 When we compare the results of our study, we can conclude that they are compatible with the intervals stated in the literature.…”
Section: Discussionsupporting
confidence: 93%
“…18 According to recent data, a retrospective data analysis study using the Pediatric Health Information System (PHIS) database, which included data from 498,956 hospitalized children from 43 different hospitals, found that 49% of hospitalizations in hospitalized pediatric patients were associated with ≥1 potential DDI. 19 Similar results were obtained in a study conducted by Daignault et al 20 When we compare the results of our study, we can conclude that they are compatible with the intervals stated in the literature.…”
Section: Discussionsupporting
confidence: 93%